PENGARUH PENGGUNAAN PENDEKATAN SAINTIFIK TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN MOTIVASI SISWA DI KELAS X SMA NEGERI 1 SIBABANGUN - feni handani sitinjak; Nabilah Siregar; Perima Simbolon (JURNAL EDUGENESIS, 2019)
ABSTRACT This study aims to know whether there is a significant correlation of using approach scientific on critical thinking ability and student’s motivation at the tenth grade students of SMA Negeri 1 Sibabangan. The research was conducted by using descriptive quantitative by applying correlational method with 35 students as the sample and they were taken by using cluster random sampling technique from 107 students. Questionnaire and observation were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of using scientific approach was 86 (very good category), (b) the average of critical thinking ability was 91% (very good category), and (c) the average of student’s motivation was 92% (very good category). Furthermore, based on inferential statistic by using Pearson correlation, the result showed (1) there is a significant correlation of using approach scientific on critical thinking ability because rtable was less than rcalculated (0.8365<0.98), and (2) there is a significant correlation of using approach scientific and student’s motivation because rtable was less than rcalculated (0.8365<0.98). Keywords: approach scientific, critical thinking ability, student’s motivation